Spectra of large diluted but bushy random graphs. Issue 1 (28th November 2015) - Enriquez, Nathanaël; Ménard, Laurent
Abstract: We compute an asymptotic expansion in 1 / c of the limit in n of the empirical spectral measure of the adjacency matrix of an Erdős‐Rényi random graph with n vertices and parameter c / n . We present two different methods, one of which is valid for the more general setting of locally tree‐like graphs. © 2015 Wiley Periodicals, Inc. Random Struct. Alg., 49, 160–184, 2016